Farming Practices of Vegetables: A Comparative Study in Four Regions of East Java and Bali Provinces - Mariyono, Joko; Dewi, Hanik A.; Daroini, Putu B.; Latifah, Evy; Zakariya, Abu Z.; Hakim, Arief L.; Afari-Sefa, Victor (AGRARIS: Journal of Agribusiness and Rural Development Research, 2018)
Agronomic and ecological aspects play important roles in vegetable production, because the aspects will be used for determining suitable interventions.  This study aims to provide current farmers’ practices of vegetable production, particularly for agronomic and ecological aspects of chilli and tomato in four regions of East Java and Bali.  This study uses of analytical tool of descriptive approach by comparing and contrasting each production practices across regions. Data were compiled from a field survey of 360 farmers during 2013-2014. Results of analysis were presented in graphical and tabular forms. Farmers mostly selected hybrid varieties of vegetables because of economic reasons, such as high yield, good appearance and high number of fruits. Anthracnose and late blight were perceived as the most important disease in chilli and tomato respectively. Farmers controlled pests and diseases using pesticides. In general, farmers perceived that irrigation was one of limiting factors of vegetable farming. Poor drainage was one of the crucial issues in Bali. Farmers mostly sold vegetable once harvested. Post-harvest handling was still traditional, where farmers still less pay attention on post-harvest, even though they observed the economic advantage of post-harvest. Based on the existing practices, a special extension on vegetable production needs to be formulated appropriately, based on the specific characteristics of each region.